Highly sensitive gas refractometers based on optical microfiber modal interferometers operating at dispersion turning point - Zhang, Nancy Meng Ying (2019)
In most fiber-optic gas sensing applications where the interested refractive index (RI) is ~1.0, the sensitivities are greatly constrained by the large mismatch between the effective RI of the guided mode and the RI of the surrounding gaseous medium. This fundamental challenge necessitates the development of a promising fiber-optic sensing mechanism with the outstanding RI sensitivity to achieve reliable remote gas sensors. In this work, we report a highly sensitive gas refractometer based on a tapered optical microfiber modal interferometer working at the dispersion turning point (DTP). First, we theoretically analyze the essential conditions to achieve the DTP, the spectral characteristics, and the sensing performance at the DTP. Results show that nonadiabatic tapered optical microfibers with diameters of 1.8-2.4 µm possess the DTPs in the near-infrared range and the RI sensitivities can be improved significantly around the DTPs. Second, we experimentally verify the ultrahigh RI sensitivity around the DTP using a nonadiabatic tapered optical microfiber with a waist diameter of ~2 μm. The experimental observations match well with the simulation results and our proposed gas refractometer provides an exceptional sensitivity as high as −69984.3 ± 2363.3 nm/RIU.